Cold Pools as Conveyor Belts of Moisture. Issue 12 (19th June 2020) - Fuglestvedt, Herman F.; Haerter, Jan O.
Abstract: Observations and simulations have found convective cold pools to trigger and organize subsequent updrafts by modifying boundary layer temperature and moisture as well as by lifting air parcels at the outflow boundaries. We study the causality between cold pools and subsequent deep convection in idealized large‐eddy simulations by tracking colliding outflow boundaries preceding hundreds of deep convection events. When outflow boundaries collide, their common front position remains immobile, whereas the internal cold pool dynamics continues for hours. We analyze how this dynamics "funnels" moisture from a relatively large volume into a narrow convergence zone. We quantify moisture convergence and separate the contribution from surface fluxes, which we find to play a secondary role. Our results highlight that dynamical effects are crucial in triggering convection, even in radiative‐convective equilibrium. However, it is the low‐level convergence resulting from this dynamics that removes inhibition, moistens the atmosphere aloft, and ultimately permits deep convection. Plain Language Summary: Cold pools are blobs of cold air that can form under thunderstorm clouds due to the evaporation of rain. Because they are denser than the surrounding air, cold pools spread out along the surface. It has long been known that thunderstorm development, while inhibited inside the cold pools, is stimulated near the edges. Here we use idealized numerical simulations of cold pool‐producing tropical thunderstorms to study how the cold pools interact to achieve this organization of subsequent clouds. We find that when cold pools collide with one another, they establish a circulation near the surface that lasts for several hours. This circulation transports air from a very large area into a small one, where it is deflected upward and eventually facilitates thunderstorm development. Our results improve our understanding of how cold pools trigger extreme rain events and have implications for how thunderstorms should be depicted in climate models. Key Points: Cold pool collisions cause a sustained reset of boundary layer circulation Tracking of colliding outflow boundaries highlights the role of premoistening in cold pool‐driven convective organization The primary cause of premoistening is sustained low‐level convergence, surface fluxes play a secondary role